2013
DOI: 10.1089/ten.tea.2012.0091
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Osteodifferentiation in Response to Alternating Electric Current

Abstract: The present study addressed adult human mesenchymal stem cell (MSC) differentiation toward the osteoblastic lineage in response to alternating electric current, a biophysical stimulus. For this purpose, MSCs (chosen because of their proven capability for osteodifferentiation in the presence of select bone morphogenetic proteins) were dispersed and cultured within electric-conducting type I collagen hydrogels, in the absence of supplemented exogenous dexamethasone and/or growth factors, and were exposed to eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 15 publications
1
47
2
Order By: Relevance
“…Prior reports in the literature present similar results with respect to osteogenesis when hMSCs were exposed to electrical stimulus in different culture settings. Two studies using electrical current on bone marrow and adipose MSCs, using collagen gels and culture dishes, respectively, found that osteogenesis increased under high currents and voltages 32, 33 . Although the stimulation conditions far exceed what was used in this study, with some reports utilizing a minimum threshold current for increased osteoblastic activity at 100μA/cm 2 34 , it demonstrates that the combination of an appropriate material with stimulation are necessary for late stage osteogenic markers to activate osteogenic differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Prior reports in the literature present similar results with respect to osteogenesis when hMSCs were exposed to electrical stimulus in different culture settings. Two studies using electrical current on bone marrow and adipose MSCs, using collagen gels and culture dishes, respectively, found that osteogenesis increased under high currents and voltages 32, 33 . Although the stimulation conditions far exceed what was used in this study, with some reports utilizing a minimum threshold current for increased osteoblastic activity at 100μA/cm 2 34 , it demonstrates that the combination of an appropriate material with stimulation are necessary for late stage osteogenic markers to activate osteogenic differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…13 Both the Creecy et al 13 and the present study used hMSCs that exhibited specific osteodifferentiation in the presence of select bone morphogenetic proteins (BMP-2 and BMP-6) alone. It should be noted, however, that the Creecy et al study did not optimize the conditions that result in osteodifferentiation of these cells under electric current stimulation.…”
Section: Resultsmentioning
confidence: 81%
“…Collagen type I, a hallmark of the osteoblast phenotype, however, was not used as an indicator of osteodifferentiation in this study because it is expressed by both undifferentiated mesenchymal stem cells and osteoblasts. 13,18 Exposure to low frequency (5 Hz), low current level (5 mA), and short duration (1 h) daily to the alternating electric current for up to 7 days, induced expression of early (specifically, TAZ and Runx-2) and middle (specifically, Osterix) osteodifferentiation genes by hMSCs (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 In order to exploit the use of electrical stimuli for bone tissue engineering, implanted materials have to possess both electrical conductivity and biocompatibility. Hence, carbon-based materials such as 3D graphene foams (GFs) could be good candidates for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%